2018
DOI: 10.1111/jace.16118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ZrO2 alloying on the microstructures and thermal properties of DyTaO4 for high‐temperature application

Abstract: High fracture toughness of 8 YSZ (8 wt% yttria‐stabilized zirconia) is linked to its ferroelastic toughening mechanism. In this work, the similar ferroelastic domain is detected in monoclinic Dy1−xTa1−xZr2xO4 ceramics, which derives from the ferroelastic transformation between the high‐temperature tetragonal (t) and low‐temperature monoclinic (m) phase. The lowest thermal conductivity of Dy1−xTa1−xZr2xO4 ceramics is reduced by 30% compared with 8 YSZ, and the largest thermal expansion coefficients (TECs) is up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Besides, the larger elastic resilience of M-phase YTaO 4 may be also relevant to the effect of its microstructure on stress. Previous researches have revealed that the ferroelastic domain analogous to twin structure existed in M-phase RETaO 4 ceramics, 21,22 which originates from its ferroelastic transition. However, according to the phase transformation principle of RETaO 4 compounds, 17 there is not ferroelastic domain in the microstructure of M' phase RETaO 4 compounds since it does not experience the reconstructive transformation from M' to T phases and the ferroelastic transition between T and M phases.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the larger elastic resilience of M-phase YTaO 4 may be also relevant to the effect of its microstructure on stress. Previous researches have revealed that the ferroelastic domain analogous to twin structure existed in M-phase RETaO 4 ceramics, 21,22 which originates from its ferroelastic transition. However, according to the phase transformation principle of RETaO 4 compounds, 17 there is not ferroelastic domain in the microstructure of M' phase RETaO 4 compounds since it does not experience the reconstructive transformation from M' to T phases and the ferroelastic transition between T and M phases.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, pure RETaO 4 , RE 3 TaO 7 , and RETa 3 O 9 have been widely studied, and in order to optimize the thermal properties, doping (including Mg 2+ , 12 Al 3+ , 13 Zr 4+ , 14,15 and Nb 5+ 16-18 ) methods and defect engineering have been shown to be an effective and promising approach. 12,15,[19][20][21][22][23] The results showed that they had lower thermal conductivity and excellent TECs compared with 7-8YSZ. 19 In addition, relevant studies have revealed that RETaO 4 has a ferroelastic domain, 24 which enhances the fracture toughness of materials.…”
Section: Methodsmentioning
confidence: 99%
“…The Birch-Murnaghan equation of state (EOS) with four parameters was employed for the polymorphous YTaO 4 to fit A survey of the published literature shows that process modeling of CMCs has been studied by a number of researchers. Processes that have been modeled include RMI, 15,16 CVD, 17,18 CVI, [19][20][21][22] and Sol-Gel Infiltration. 23 Impregnation of alumina matrix in eight-harness satin Nextel 610 fabric has been studied numerically in Ref.…”
Section: Computational Methods and Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…NiO/CoO added into LaNbO 4 would distinctly optimize the quality factor since the larger and uniform grain was obtained [192]. Although the thermal properties [193][194][195][196] and the first-principles calculation of electronic structure and optic properties of RETaO 4 (RE = Y, La, Sm, Eu, Dy, Er) [197] have been investigated, the intrinsic dielectric loss has not been summarized in this system. Microwave dielectric properties of ErNbO 4 prepared by sol-gel method were reported by Devesa et al [198], and the grain size varied from 31.27 to 86.65 µm and 40.96 to 78.23 µm by Rietveld refinement and Sherrer's formula, respectively.…”
Section: Retico 6 Ceramicsmentioning
confidence: 99%